2021
DOI: 10.1177/09612033211038824
|View full text |Cite|
|
Sign up to set email alerts
|

Hematological involvement in pediatric systemic lupus erythematosus: A multi-center study

Abstract: Introduction: Systemic lupus erythematosus (SLE) may present with features of several systems, including hematological manifestations. In this study, we aimed to evaluate the characteristics of hematological involvement and assess possible associations and correlations in pediatric SLE patients. Method: This is a retrospective multi-center study. The medical records of pediatric SLE patients followed between January 2000 and June 2020 were analyzed. All children fulfilled the criteria of the Systemic Lupus Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Moreover, we found that APLA antibodies were more frequently encountered in patients with AIHA, similar to the results in the literature. 13,20 Our results also showed a moderate negative correlation between hemoglobin levels and SLEDAI score, erythrocyte sedimentation rate, and serum ferritin levels. Similar to our results, a study on adult patients with SLE patients found that inflammatory status was associated with anemia and reported a negative correlation between ferritin and hemoglobin levels.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Moreover, we found that APLA antibodies were more frequently encountered in patients with AIHA, similar to the results in the literature. 13,20 Our results also showed a moderate negative correlation between hemoglobin levels and SLEDAI score, erythrocyte sedimentation rate, and serum ferritin levels. Similar to our results, a study on adult patients with SLE patients found that inflammatory status was associated with anemia and reported a negative correlation between ferritin and hemoglobin levels.…”
Section: Discussionsupporting
confidence: 68%
“…Our results showed hematologic involvement in two-thirds of patients at onset, which was similar to previous studies that reported ranges of up to 88%. [10][11][12][13] In addition, anemia was the most frequently observed cytopenia, followed by lymphopenia and leukopenia in our study. Studies with SLE patients often investigated the hematologic findings included in the classification criteria such as AIHA, lymphopenia, leukopenia, and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“… 2 , 3 Hematological abnormalities are common in children with SLE, with an incidence of 34% to 82.7%. 4 Anemia, thrombocytopenia, and leucopenia are common hematological manifestations in pediatric SLE patients. 4 Hematological involvement may result from bone marrow failure or excessive peripheral cell destruction, both of which may be immune-mediated.…”
Section: Introductionmentioning
confidence: 99%